Designing the entrepreneurial education model - Mohammadtaghi Toghrāyi; Seyyed Saeed Mirvāhedi; somayeh hashemi (فصلنامه نوآوری‌های آموزشی, 2019)
Nowadays, in almost all of the developed and developing countries at all educational levels, the education and promotion of the entrepreneurship have a special place, so that innovation at the different dimensions of the education system underlies the education of a creative and multidimensional generation. The main purpose of the present study was designing theentrepreneurial education model at schools. It was an applied research with grounded theory design. The research population included all educational authorities and experts, educational management and planning, psychology and sociology experts, as well as the entrepreneurial education authorities. Using the theoretical sampling method, research findings reached the theoretical saturation, after conducting 30 in-depth interviews. The results showed that the value creation - based education is the main and key dimension of the entrepreneurial education which is influenced by the triggering factors of the entrepreneurial attitude of the parents, schools’ authorities and decision makers and teachers. The most important contextual factors including the entrepreneurial atmosphere, designing the playful environment, designing the attractive spaces of school along with the environmental conditions such as entrepreneurial consciousness, educational planning and entrepreneurial awareness help to implement and adopt strategies and actions including training along with performance, entrepreneurial learning, entrepreneurial assignments, entrepreneurial teams, entrepreneurial curiosity, the school interaction with the real-world, flexible and multilateral evaluation, and emphasis on cognition and metacognition. Finally, creating the new values, educating the creative, innovative and multi-dimensional student and empowered-skillful student could be the main consequence and output of the entrepreneurial education at school, during which the students deal with creating value for themselves and their society, while being on the correct educational and career path.